2011
DOI: 10.1073/pnas.1102828108
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific collaboration of heat shock proteins (Hsp) 70 and 100 in thermotolerance and protein disaggregation

Abstract: Yeast Hsp104 and its bacterial homolog, ClpB, are Clp/Hsp100 molecular chaperones and AAA+ ATPases. Hsp104 and ClpB collaborate with the Hsp70 and DnaK chaperone systems, respectively, to retrieve and reactivate stress-denatured proteins from aggregates. The action of Hsp104 and ClpB in promoting cell survival following heat stress is species-specific: Hsp104 cannot function in bacteria and ClpB cannot act in yeast. To determine the regions of Hsp104 and ClpB necessary for this specificity, we tested chimeras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
174
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(186 citation statements)
references
References 35 publications
11
174
0
1
Order By: Relevance
“…It is of interest that many of the consensus motifs are enriched in hydrophobic residues (Leu, Ile, Val, Phe, and Tyr), which are often found in Hsp70 substrates (38). Importantly, we found that the location of consensus motifs within M-domain helix 2 (motifs E and F) overlapped with mutation sites in Escherichia coli ClpB, which either impaired ClpB's innate protein disaggregating activity or affected the functional cooperation between ClpB and DnaK/DnaJ/GrpE in substrate recovery (34). For instance, Hsp70 ΔC recognized both Lys442/ Asp443/Arg444 (motif E) and His471/Glu474/Glu475 (motif F) (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…It is of interest that many of the consensus motifs are enriched in hydrophobic residues (Leu, Ile, Val, Phe, and Tyr), which are often found in Hsp70 substrates (38). Importantly, we found that the location of consensus motifs within M-domain helix 2 (motifs E and F) overlapped with mutation sites in Escherichia coli ClpB, which either impaired ClpB's innate protein disaggregating activity or affected the functional cooperation between ClpB and DnaK/DnaJ/GrpE in substrate recovery (34). For instance, Hsp70 ΔC recognized both Lys442/ Asp443/Arg444 (motif E) and His471/Glu474/Glu475 (motif F) (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The Hsp104 M-domain coiled-coil is composed of four α-helices, which can be subdivided into two smaller coiled-coils, termed motif 1 and motif 2 (5,6). It was previously shown that mutations in the ClpB M-domain helix 2 had a small but significant effect on substrate recovery (34), whereas mutations in helix 3 abrogated protein disaggregation (35), which was attributed to a potentially impaired interaction between ClpB and DnaK (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of a direct ClpB-DnaKJ/GrpE interaction, it was reported that ClpB interacts with DnaK via the ClpB M-domain (15,26). Notably, replacing the M-domain of bacterial ClpB with that of its yeast homolog Hsp104 switched the species specificity of the bichaperone system so that ClpB now cooperated with the eukaryotic Hsp70/40 system and vice versa (7,27). The role of the M-domain in mediating DnaKJ/GrpE interaction is consistent with the M-domain being on the outside of the ClpB hexamer (5,8), but incompatible with the previously proposed structure of yeast Hsp104 (28,29), which placed the M-domains on the interior or intercalated between subunits.…”
mentioning
confidence: 99%